Analisis Pengaruh Produk Domestik Regional Bruto (PDRB) Dan Suku Bunga Terhadap Investasi Swasta Sektor Pertanian Di Sumatera Barat Periode Tahun 2014-2024 - Dedi Julianto; Firsta Ninda Rosadi; Mieke Efrianda; Azel Febrya Putri (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2026)
This study, entitled "Analysis of the Effect of Gross Regional Domestic Product (GRDP) and Interest Rates on Private Investment in the Agricultural Sector in West Sumatra for the 2014-2024 Period," aims to analyze the effect of GRDP and interest rates on private investment in the agricultural sector in West Sumatra between 2014 and 2024. The data used are secondary time series data obtained from the Central Statistics Agency (BPS) of West Sumatra Province and the International Financial Statistics Agency (IFS). The analytical method used is Ordinary Least Squares (OLS) regression, with a predetermined equation model. The results indicate that GRDP has a significant positive relationship with private investment in the agricultural sector, while interest rates show a negative relationship. This study provides important insights into the factors influencing investment in the agricultural sector, which can serve as a reference for policymakers and investors.